Pengaruh Media Tanam terhadap Pertumbuhuan Kacang Hijau (Vigna Radiata) - Depi Yanti Nasution; Nadya Wahyuni Hasibuan; Rusdiah Murni Nasution; Indayana Febriani Tanjung (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
There are various types of planting media, but not all types of planting media are suitable for growing certain types of plants. The planting medium used must be adjusted to the type of plant to be planted. A good planting medium for plant growth must have good physical properties, be loose and have the ability to hold water. The planting medium is a place where plants grow and develop, so it needs special arrangements and treatment. Using soil growing media alone is not enough to support plant growth and yields, so it is necessary to add organic materials that can provide nutrients and provide loose soil texture and the ability to store water. Mung bean is an annual plant which is quite widely cultivated in Indonesia. Green beans themselves are included in tropical plants and their cultivation is quite easy. Green beans (vigna radiata) as a source of vegetable protein. Another advantage of mung bean plants is that they are early maturing or short, mung bean plants are also tolerant of drought because they are deeply rooted and can grow on soils that are poor in nutrients so they can be cultivated on marginal lands. Climatic conditions desired by green bean plants to be able to grow and produce well in lowland areas up to an altitude of 500 meters above sea level with optimal rainfall of 50 - 200 mm/month, temperature 25 - 27 â°C, humidity 50 - 80% and enough light sun.